Neural rerankers for dependency parsing - Do, Bich-Ngoc; Rehbein, Ines (Universität, 2023)
This resource contains code for different types of neural rerankers (RCNN, RCNN-shared and GCN) from the paper: Do and Rehbein (2020). "Neural Reranking for Dependency Parsing: An Evaluation". We also include in this resource the pre-trained models of different rerankers on 3 languages: English, German and Czech that are used to report results in the paper.
Produktionsdatum: 2020
Gesehen am 22.11.2023
Keywords: Forschungsdaten; Datenbank